Dual function of Bmpr1a signaling in restricting preosteoblast proliferation and stimulating osteoblast activity in mouse - Lim, Joohyun (Development, 2016)
Exogenous bone morphogenetic proteins (Bmp) are well known to induce ectopic bone formation, but the physiological effect of Bmp signaling on normal bone is not completely understood. By deleting the receptor Bmpr1a in osteoblast lineage cells with Dmp1-Cre, we observed a dramatic increase in trabecular bone mass in postnatal mice, which was due to a marked increase in osteoblast number that was likely to be driven by hyperproliferation of Sp7(+) preosteoblasts. Similarly, inducible deletion of Bmpr1a in Sp7(+) cells specifically in postnatal mice increased trabecular bone mass. However, deletion of Smad4 by the same approaches had only a minor effect, indicating that Bmpr1a signaling suppresses trabecular bone formation through effectors beyond Smad4. Besides increasing osteoblast number in the trabecular bone, deletion of Bmpr1a by Dmp1-Cre also notably reduced osteoblast activity, resulting in attenuation of periosteal bone growth. The impairment in osteoblast activity correlated with reduced mTORC1 signaling in vivo, whereas inhibition of mTORC1 activity abolished the induction of protein anabolism genes by BMP2 treatment in vitro. Thus, physiological Bmpr1a signaling in bone exerts a dual function in both restricting preosteoblast proliferation and promoting osteoblast activity.